EndoPRIME - Prehabilitation and exercise before arthroplasty - Seefried, Lothar; Luksche, Nicole; Schneider, Michael; Genest, Franca (PeerJ PrePrints, 2015)
Over the last two decades the number of total joint replacement surgeries increased consistently. With the patient population growing older and therefore suffering from more comorbidities and total joint replacement being progressively indicated even in patients with compromised medical status, the need for preoperative optimization of medical conditions appears a promising approach to reduce perioperative risk for complication, and readmission rates, avoid prolonged functional deficiency and improve functional, objective as well as patient reported, subjective outcome following surgery. Literature addressing the question of preoperative status afflicting postoperative outcome after total joint replacement is still imprecise and inconsistent. There seems to be some data, that a worse preoperative functional status predicts worse outcome in terms of both function and pain after total joint replacement. It is still not clear, what preoperatively evaluable parameters can be modified by which kind of intervention and which measures are suitable to monitor improvement of the outcome following such interventions. Based on the hypothesis that patient reported outcome, the frequency of untoward events and functional outcome following total joint replacement can be improved by establishing an individualized concept aiming at improving medical conditions and physical performance preoperatively, the EndoPRIME Trial (ENDOprosthetic joint replacement – improving treatment by integrating Prehabilitation, Rehabilitation, Individualized Management and Education) was initiated. The trial was approved by the competent ethics committee at Wuerzburg University. The project aims at expanding current knowledge about the feasibility and potential of preoperative improvement and quantivfy respective effects on postoperative outcome after total joint replacement, The proposed study is an interventional, prospective, single-center pilot study with exploratory data analysis to evaluate the feasibility and potential of improving peri- and postoperative outcome in total joint replacement of the hip, knee and shoulder by a standardized, individually optimized treatment pathway including pre- and postoperative exercising, risk management and patient education based on a comprehensive preoperative functional assessment and expanded clinical evaluation. Study duration for each individual patient comprises 12 weeks prior to surgery and one year after surgery, i.e. individual participation will last weeks. The primary endpoint of the trial is intraindividual development of osteoarthritis-associated health-limitations as measured by the WOMAC-Score. Further objectives include Patient Reported Outcome measures, type and frequency of perioperative untoward events, and a wide range of clinical and technical assessments of physical performance. Results can be expected by the third quarter 2017.
Keywords: Prehabilitation; Arthroplasty; Musculosceletal; Osteoporosis; Sclerostin; Frailty; Sarcopenia; Bone Metabolism; Physical activity